Encountering Ability : On the Relational Nature of Human Performance. (Value Inquiry Book Series, 2016)
In Encountering Ability , Scott DeShong considers how ability and its correlative, disability, come into existence. Besides being articulated as physical, social, aesthetic, political, and specifically human, ability signifies and is signified such that signification itself is always in question. Thus the language of ability and the ability of language constitute discourse that undermines foundations, including any foundation for discourse or ability. Drawing on Gilles Deleuze's theory of primary differentiation and Emmanuel Levinas's philosophy of ethical relationality, Encountering Ability finds implications of music, theology, and cursing in the signification of ability, and also examines various literary texts, including works by Amiri Baraka and Marguerite Duras.